MANAJEMEN SHARED KNOWLEDGE DALAM PRAKTIK KAMPANYE (Analisis Wacana Filosofi Silas pada Grup Facebook Simpatisan Dedi Mulyadi) - Mochamad Faris Dzulfiqar, - (2020)
This research is exploring discourse as a social practice in the Deddy Mizwar-Dedi Mulyadi (2DM) sympathizer campaign activity qualitatively. There are 37 data gathered from five Facebook groups for this research. Discourse analysis approach with discourse tracing technique is utilized as a means to observe how a discourse become routinized within a practice according to its interaction in between each discourse level, such as macro (news article), meso (fans page article), and micro (user status). The result suggests that silas discourse is conduct to managing shared knowledge during campaign activity, but not limited to the construction of issue and candidates image, however also changing the campaign initial condition to allowing spiritualization by doing Ki Sunda's biographical knowledge production. The knowledge of a shared experience during the struggle for Dedi Mulyadi, which seen by the sympathizers in 'Siliwangi jaman kiwari' position with a vision of 'Sajajar society'. By doing this, silas philosophy directing Sundanese local wisdom to environmental concern with the religious mindset, also being experienced as a call to self-identification to Sundanese culture authentically (kaaingan). Thus, shared knowledge management is a process to transforming documentation of campaign activity into Ki Sunda's biographical knowledge production with spiritual zeal known as 'sagacious selfhood' - a mindset about the self that viewed from Sundanese local wisdom with holistic worldview among self, God, and nature interdependent. Key Words: ecocentrism, philosophy of silas, sagacious selfhood